CIFOR’s testing on a minimum set of criteria and indicators in PT INHUTANI II, Stagen, Pulau Laut, South Kalimanta, Indonesia. - Purnadjaja; Indrawan, A.; Siregar, C.A.; Muhtaman, D.R.; Purwanto, S.A.; Warsito, S.P.; Darma, I.G.K.T (Center for International Forestry Research, 1998)
Critical increase of world population growth has revealed significant consequences in terms of food and wood needs for people on the globe. This alarming phenomenon inevitably gave rise to major changes on land use form or natural vegetation covered the earth surface due to the population pressure occured on readily available natural resources such as tropical rain forest. In order to fulfill the basic needs of food and wood through agricultural cultivation in one hand and to ease degradation rate of natural forest on the other hand, forest plantation have been established in many countries included Indonesia during the last two decades. Owing to the fact mentioned before, up to date, plantation forest has been an important land use system especially in the tropical area. For example Indonesian goverment has projected to establish 6.2 million hectares of industrial forest plantation by the year 2000. In so far as ecological aspect is considered, that plantation forest are expected to play the important role of the productive and protective functions of the natural forest. However, some industrial forest plantations have been reported as an alternative technology causing not only environmental problems through reduction in species biodiversity, soil erosion, water pollution and stream bed sedimentation, but also socio-economical problems such as low market price due to over production, and conflicts between villagers and forest concession holder. To cope up with the overall adversed effects may rise from the plantation forest project, sustainable forest management has been espoused as the key tool by scientists from many countries all over the world. This sustainable forest management concept is therefore designed to ensure that the establishment of industrial forest plantation satisfy economic, ecology and social functions as compared to natural forests. In turn, to examine whether the sustainable forest management practices is still on the right tract with overall objectives, a comprehensive method of evaluation is needed. Currently, the concept of principles, criteria and indicator (P, C&I) has been developed in the forest sector as a method or guidelines to determine and evaluate sustainable forest management a the international, national and forest management unit level. Since its existence, Criteria and Indicator (C&I) have been developed by many institutions. For example, ITTO comes up with principles of sustainable forest management (SFM); WWF develops guidelines; FSC introduces general Principle, Criteria and Indicators; Smart Wood Program of Rainforest Alliance introduces its C&I; Lembaga Ekolabel Indonesia (LEI) also develops C&I for production forest. These variety of C&I can be applied at various levels: global, regional (eco-regional), national, and sub-national or at Forest Management Unit (FMU) level. However, one source of C&I is not necessarily applicable at all local/FMU level. Due to the significance of socio-economic and ecology are variable across the whole countries and forest management unit as well, the guidelines consisting P, C&I are unlikely final. In other words, set of P, C&I for use at any level is supposed to be developed to assess the quality of management and ecosystem in question in a way toward the achievement of sustainable goal. Therefore, CIFOR through project " Testing Criteria and Indicators for Sustainable Forest Management" has been trying to search C&I that fits with particular FMU, in this case, in Indonesia. The similar test also will be conducted in Brazil and Coté d'Ivore. The final findings of C&I are expected to generate a minimum number of cost effective and reliable C&I for each test site, based on iterative and comparative field evaluation of selected sets